2016
DOI: 10.1016/j.ejsobi.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal tolerant Pseudomonas protegens isolates from agricultural well water in northeastern Algeria with plant growth promoting, insecticidal and antifungal activities

Abstract: The application of plant growth-promoting bacteria (PGPB) with biocontrol activities as inoculants of crops plants against phytopathogenic fungi and insect pests provides a biological alternative to the use of agrochemicals. Two Pseudomonas sp. strains were isolated from agricultural well water in the area of Bejaia, northeastern Algeria, located rather closely to a lead mine deposit. The isolates S4LiBe and S5LiBe had 16S rRNA gene sequence similarities of 99.4% to 99.7% with Pseudomonas protegens CHAO T and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Koo and Cho (2009) showed that Serratia plymuthica SY5 isolated from heavy metal contaminated soil had capacity for IAA production and root growth potential. A previous report also indicated that P. protegens strains can produce IAA and stimulate plant growth ( Bensidhoum et al, 2016 ). In our study there was no direct relationship between the IAA producing ability of strains and root growth promoting effects.…”
Section: Discussionmentioning
confidence: 86%
“…Koo and Cho (2009) showed that Serratia plymuthica SY5 isolated from heavy metal contaminated soil had capacity for IAA production and root growth potential. A previous report also indicated that P. protegens strains can produce IAA and stimulate plant growth ( Bensidhoum et al, 2016 ). In our study there was no direct relationship between the IAA producing ability of strains and root growth promoting effects.…”
Section: Discussionmentioning
confidence: 86%
“…strain CdDB50). This genus is well recognized due to its heavy metal bioremediation ability (Bensidhoum et al 2016). We strongly recommend the use of Pseudomonas sp.…”
Section: Cdtb Bacteria In Cacao Soilmentioning
confidence: 97%
“…Previous reports also indicated that P. protegens (formerly P. fluorescens) strains had a high ability to solubilize phosphate or were able to produce IAA and siderophores, resulting in improved plant growth (Bensidhoum et al, 2016;Katiyar & Goel, 2003). The endophytic life strategy of Stenotrophomonas maltophilia strains with various plants and an ability to promote plant growth are also documented (Ryan et al, 2009).…”
Section: Evaluation Of Plant Growth Promotion Abilitymentioning
confidence: 98%